2007
DOI: 10.1111/j.1538-7836.2007.02776.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen deficiency

Abstract: Summary.  Plasminogen (plg) deficiency has been classified as (i) hypoplasminogenemia or ‘true’ type I plg deficiency, and (ii) dysplasminogenemia, also called type II plg deficiency. Both forms, severe hypoplasminogenemia and dysplasminogenemia, are not causally linked to venous thrombosis. Dysplasminogenemia does not lead to a specific clinical manifestation and probably represents only a polymorphic variation in the general population, mainly in Asian countries. Severe hypoplasminogenemia is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
171
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 88 publications
(141 reference statements)
2
171
0
9
Order By: Relevance
“…An illustrative example of such a defect is deficiency of the serine protease, plasminogen, which was long described as a disease affecting only the eyes and the conjunctiva but now is well established as a systemic disease affecting multiple epithelia. 44 In summary, this study has revealed an essential role of matriptase in the maintenance of global epithelial homeostasis in the mouse and has provided an important animal model for the further exploration of matriptase function in multiple physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…An illustrative example of such a defect is deficiency of the serine protease, plasminogen, which was long described as a disease affecting only the eyes and the conjunctiva but now is well established as a systemic disease affecting multiple epithelia. 44 In summary, this study has revealed an essential role of matriptase in the maintenance of global epithelial homeostasis in the mouse and has provided an important animal model for the further exploration of matriptase function in multiple physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that the hyperfibrinolytic state is related with expanded propensity to drain, lack of the same inclines to thromboembolism. [29] Excessive enactment of fibrinolysis might be seen amid cardiopulmonary sidestep, thus antifibrinolytics have a valuable part in the aversion of same.…”
Section: Clutters Of Fibrinolysismentioning
confidence: 99%
“…Similar splice‐site mutations have previously been noted in affected humans with LM (Schuster et al . 2007). The non‐carriage of c.1256+2T/A in 24 normal Scottish Terriers indicates that carriers of the mutation are generally not common in this breed.…”
mentioning
confidence: 99%
“…2008), the literature for humans supports hypoplasminogenemia as the most likely cause of LM (Schuster et al . 2007). Therefore, it is difficult to explain the apparently normal plasminogen activity in the affected male.…”
mentioning
confidence: 99%